2020
DOI: 10.3389/fpls.2020.01138
|View full text |Cite
|
Sign up to set email alerts
|

Barley ABI5 (Abscisic Acid INSENSITIVE 5) Is Involved in Abscisic Acid-Dependent Drought Response

Abstract: ABA INSENSITIVE 5 (ABI5) is a basic leucine zipper (bZIP) transcription factor which acts in the abscisic acid (ABA) network and is activated in response to abiotic stresses. However, the precise role of barley (Hordeum vulgare) ABI5 in ABA signaling and its function under stress remains elusive. Here, we show that HvABI5 is involved in ABAdependent regulation of barley response to drought stress. We identified barley TILLING mutants carrying different alleles in the HvABI5 gene and we studied in detail the ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 97 publications
(181 reference statements)
4
49
0
Order By: Relevance
“…Following this, hydrogen peroxide reduction is catalyzed by a peroxidase which removes active oxygen. Collin et al confirmed that increased expression of POD and SOD reduces drought-induced damages in barley (Collin et al, 2020 ). This study found that under drought stress and rewatering, lower SOD and POD activities were measured in the BMV-ZmbZIP33 mutant than BMV ( Figures 6C,D ).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Following this, hydrogen peroxide reduction is catalyzed by a peroxidase which removes active oxygen. Collin et al confirmed that increased expression of POD and SOD reduces drought-induced damages in barley (Collin et al, 2020 ). This study found that under drought stress and rewatering, lower SOD and POD activities were measured in the BMV-ZmbZIP33 mutant than BMV ( Figures 6C,D ).…”
Section: Discussionmentioning
confidence: 92%
“…In Barley, overexpression of HvABI5 increases HvSnRK2.1 expression, enabling the amplification of ABA signaling and activation of ABA-related genes. Under drought stress, HvABI5 directly upregulated of ABA synthesis, and ABA signaling via induction of HvPP2C4 and HvSnRK2.1 in response to drought stress (Collin et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The ABA signaling pathway mainly relies on OsbZIP transcription factors, including AREBs, ABFs, and ABI5. Among these, ABI5 plays a key role in suppressing ABA-mediated seed germination and post-germination growth in a number of plant species, such as Arabidopsis [13,40,41], rice [42], wheat [43,44], barley [45], and Sorghum [46]. In addition to the roles of these classical bZIP transcriptional factors in the ABA pathway, several other bZIP members are also involved in the ABAmediated regulation of seed dormancy and germination in rice.…”
Section: Discussionmentioning
confidence: 99%
“…ABREs are major cis-acting regulators in ABA-dependent gene expression ( Kim et al, 2004 ; Wang et al, 2019 ; Chen et al, 2020 ). ABI3, ABI4, and ABI5 bind directly to the ABREs of the promoter regions of a subset of genes, thereby controlling their transcription levels ( Carles et al, 2002 ; Ezcurra et al, 2000 ; Mizoi et al, 2012 ; Shu et al, 2013 ; Skubacz et al, 2016 ; Wang et al, 2019 ; Chandrasekaran et al, 2020 ; Collin et al, 2020 ). Notably, ABI3, ABI4, and ABI5 either activate or repress gene expression in diverse processes depending on DNA binding.…”
Section: Introductionmentioning
confidence: 99%